INVESTIGATING THE BEHAVIOR OF PILED RAFT FOUNDATION IN CORE WALL FOUNDATION OF HIGH-RISE BUILDINGS - Nguyen Anh, Tuan (Journal of Applied Engineering Science, 2021)
Core structure is an indispensable part of high buildings. Normally, the foundation of the core structure has a raft of larger size than the other foundations in the same project; therefore, the foundation of the core structure can be viewed as a small piled raft foundation. Currently, when calculating the piled foundation of the core, it is mostly assumed that the piles system will bear all the project loads. But this calculation method is not suitable for the actual constructions as well as does not make full use of the bearing capacity of the structure and the ground, leading to using more materials and causing more waste. Core structure aims to increase both stiffness and horizontal load capacity in high-rise buildings, so the moment inside the core transmitted to the foundation is very large. One of the shortcomings of the Plaxis 3D Foundation software is its inability to declare the moment affecting on the foundation due to the loads in this program just includes distributed loads, line loads and point loads in the geometry model. Consequently, when using Plaxis 3D Foundation software to calculate the core wall foundation of high-rise buildings, this moment is converted into an equivalent pair of moments. The research shows that when the core foundation of a high-rise building is placed on soft soil, the pile carries 96%, most of the load transmitted to the foundation. However, when the foundation is placed on hard soil, the soil surrounding the raft will bear about 10% of the load transmitted to the foundation. If this matter is skipped, there will be a large error in calculation and design
Keywords: piled raft foundation, FEM, soft soil, high-rise buildings, moment